2015
DOI: 10.1590/01000683rbcs20150326
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability and Vitality of Epigeous Termite Mounds in Pastures of Mato Grosso Do Sul, Brazil

Abstract: Epigeous termite mounds are frequently observed in pasture areas, but the processes regulating their population dynamics are poorly known. This study evaluated epigeous termite mounds in cultivated grasslands used as pastures, assessing their spatial distribution by means of geostatistics and evaluating their vitality. The study was conducted in the Cerrado biome in the municipality of Rio Brilhante, Mato Grosso do Sul, Brazil. In two pasture areas (Pasture 1 and Pasture 2), epigeous mounds (nests) were georef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…To calculate the area occupied by termite mounds, seven studies were used, all carried out in Brazilian Cerrado (Figure 1). Moreover, it was assumed that 88% of termite mounds are active, according to Lima et al (2015), Senci and Junqueira et al (2013), Lima et al (2011), and Cunha and Morais (2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To calculate the area occupied by termite mounds, seven studies were used, all carried out in Brazilian Cerrado (Figure 1). Moreover, it was assumed that 88% of termite mounds are active, according to Lima et al (2015), Senci and Junqueira et al (2013), Lima et al (2011), and Cunha and Morais (2010).…”
Section: Methodsmentioning
confidence: 99%
“…Boddey et al (2004) suggested that at least 50% of Brazilian pastures were in advanced degradation stages, with low grass yield and soil cover, invaded by weeds, and in many cases densely occupied by termite mounds. In addition, in degraded Cerrado pastures, the mound-building termite population is usually high (Lima et al, 2015). According to Cunha and Morais (2010), the density increment of termite mounds in pastures could occur due to the homogeneity of the environment and less competitors/predators.…”
Section: Figure 2 -mentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 40 mounds of the two most consumed species ( Macrotermes falciger and Macrotermes natalensis ) in the Vhembe District (Netshifhefhe et al., 2018) were randomly selected from all land‐use types and their dimensions (height, basal circumference and estimation of diameter) were measured using a measuring stick and measuring tape (Collins, 1981; Debelo & Degaga, 2014; Lima et al., 2015; Sands, 1961). The widest diameter and circumference were measured at ground level (where change in soil colour was visible or where changes in slope were noticeable), and the height measured using folded 2‐metre ruler (Kelly & Samways, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Spatial distribution patterns of foraging populations of termites have been studied using various methods such as the nearest-neighbour technique for distance index (Korb and Linsenmair 2001), geostatistical techniques, Ripley's K function and pair correlation function for epigeal mound and subterranean population distributions (Crist 1998, Grohmann et al 2010, Lima et al 2015. Arifin et al (2014) reported in South Sumatra Palembang, Indonesia, the randomly distribution of epigeal mounds built by Macrotermes spp.…”
Section: Introductionmentioning
confidence: 99%